Converting the sociotechnical convergence hazards into the risks of digitalisation - V. V. Zotov; I. A. Aseeva; V. G. Budanov; V. A. Belkina (Цифровая социология)
The creation of digital network platforms is accompanied by an ambiguous process of sociotechnical convergence, during which certain hazards arise as factors that destabilize the functioning of a digital platform, and risks as an expectation of the occurrence of these events.   The purpose of the study is to assess the level of conversion of the sociotechnical convergence hazards into the corresponding risks.   The research methodology is based on the ecosystem approach and the concept of platform research, supplemented by the authors with the ideas of sociotechnical convergence.   To study the conversion of the sociotechnical convergence hazards into the risks of digitalization, the method of empirical verification based on a representative sociological survey was applied. Theresult of the taxonomic division was the classification of hazards in such subject areas as (hazard of failure); digital surveillance (hazard of excessive digital surveillance); digital morality (hazard of decision-making by artificial intelligence); digital identification (hazard of identification error); digital privacy (hazard of unauthorized use of personal data); digital communication (hazard of virtualization of social contacts); digital accessibility (hazard of digital inequality); digital clusters (hazard of social network segmentation); digital competence (hazard of digital outsider). The authors come to the conclusion that not all hazards are converted into risks in the same way. Strongly expressed explicit risks are observed as a result of converting the hazard of unauthorized use of personal data. Medium-expressed explicit risks appear in case of hazard of failure of digital platforms, hazard of decision-making by artificial intelligence, hazard of identification error, hazard of digital inequality. Weakly expressed explicit risks are typical for the conversion of the hazard of excessive digital surveillance and the hazard of virtualization of social contacts. The hazard of social network segmentation and the hazard of digital outsider are converted into implicit risks.